Low power consumption thermooptic switch using polymers - Supa'at, A. S. M.; Mohammad, Abu Bakar; Kassim, N. M.; Idrus, S. M. (2005)
Thermooptic 2times2 switches utilizing polymer technology is reported. The devices made of ultraviolet curable fluorinated polymer are based on directional coupler. The waveguide is a rectangular buried channel type with 7times7 mum and the effective index difference of the channel waveguide is about 0.5% for single mode operations. The crosstalk of the switching state is more than 36 dB. The fabricated switch exhibits very low switching power of 32.4 mW.